Kawasaki disease and its relationship to Covid-19 (Research, Society and Development, 2022)
Introduction: Children affected by Covid-19, the picture of hyperinflammation presented showed changes in the coronary arteries, characteristic of Kawasaki disease (KD). Children present with persistent high fever, rash, swelling of the extremities, non-purulent conjunctivitis, abdominal pain, vomiting, and diarrhea. Objective: to present the scientific evidence available so far, which brings an existing association between Kawasaki Covid-19 Disease in children. Methodology: This is a literature review carried out between June and July 2021, in the following databases: Virtual Health Library (VHL), Google Scholar, Scientific Electronic Library Online (SciELO) and National Library of Medicine (PubMed MEDLINE). Results and discussion: It is suggested that the mechanism of KD is based on an antibody-mediated post-inflammatory reaction, thus, the identification of viral replication was not truly relevant in these cases. In addition to the link between the Covid-19 pandemic and the increase in DK cases, another period where there was a peak in DK incidence was during the context of the H1N1 pandemic, suggesting that SARS-CoV-2 is not the only virus capable of trigger such emergence of Kawasaki disease. Conclusion: Despite the more severe manifestations in patients affected by Covid-19, the occurrence of KD associated with Covid-19 is not very frequent, however, it is important to be aware of the signs and symptoms of the disease in order to obtain the earliest possible diagnosis. and proceed with the appropriate treatment, in order to avoid the occurrence of complicated or aggravated clinical conditions.